Photodynamic Inactivation of Bacteria Using Nickel(II) Complexes with Catecholate and Phenanthroline Ligands - Devraj Prakashchandra R.; Rai R.; Ali Mandal A.; Dhar P.; Banerjee S.; Sarkar T.; Nagendra Babu B. (My University, 2025)
Metal complexes activated by light can combat infections by triggering the photodynamic inactivation of bacteria. Herein, we report six mixed-ligand nickel(II) complexes with the formulation [Ni(NN)2(L)] (1–6), where NN represents an N,N-donor phenanthroline ligand, specifically 1,10-phenanthroline (phen in 1, 2), dipyrido[3,2-d:2’,3’-f]quinoxaline (dpq in 3, 4), and dipyrido[3,2-a:2’,3’-c]phenazine (dppz in 5, 6), while L is an O,O donor bidentate ligand derived from catechol (cat2−, in 1, 3, 5) or esculetin (esc2−, in 2, 4, 6). The paramagnetic d8 octahedral complexes demonstrated good dark and photostability in the solution phase and exhibited significant light absorption in the visible (400–700 nm) region. When exposed to low-energy visible light, these complexes demonstrated significant photodynamic inactivation activity against both Gram-(+) Staphylococcus aureus (S. aureus) and Gram-(−) Escherichia coli (E. coli) bacteria. This resulted in minimum inhibitory concentration (MIC) values ranging from 0.31–9.49 μM. The activity was caused by the cell-damaging singlet oxygen species produced by the complexes under light exposure. Notably, the complexes showed no bacterial inhibition activity under dark conditions. This study marks the first examples of Ni(II) complexes designed for light-triggered antibacterial activity, illuminating the path for Ni(II)-based non-macrocyclic complexes for antibacterial PDT applications. © 2024 Wiley-VCH GmbH.